An Introduction to the Chinese economy : the driving forces behind modern day China - Guo, Rongxing (Hoboken : John Wiley & Sons, 2011)
This comprehensive overview of the modern Chinese economy by a noted expert from China offers a quality and breadth of coverage. In this book, the author provides an introduction to China's economy since 1949 and original insights based on his own extensive research. The book sets out to analyze and compare the operational mechanisms of the Chinese economy between the pre- and post-reform periods and through national, regional and local dimensions. Both positive and negative consequences of the Chinese economic transformation have been clarified. A multiregional comparison of the Chinese econo.
Print version record.
Keywords: Since 1949; Business; BUSINESS & ECONOMICS -- Development -- Business Development; BUSINESS & ECONOMICS -- Development -- Economic Development; BUSINESS & ECONOMICS -- Development -- General; BUSINESS & ECONOMICS -- Government & Business; BUSINESS & ECONOMICS -- Structural Adjustment; POLITICAL SCIENCE -- Public Policy -- Economic Policy; Business; Economic history; Economic policy; China -- Economic conditions -- 1949-; China -- Economic policy -- 1949-; China; Electronic books